Front Cover. Issue 7 (25th July 2022) - Dires, Abebe; Kebede, Assen; Gedamu, Sisay; Dires, Tadila
Abstract : The cover image is based on the Case Study Case of multiple furuncular myiasis in Northeast Ethiopia by Abebe Dires et al., https://doi.org/10.1002/ccr3.6015 .